Laser-induced formation of bismuth nanoparticles. Issue 20 (11th May 2018) - Assis, Marcelo; Cordoncillo, Eloísa; Torres-Mendieta, Rafael; Beltrán-Mir, Héctor; Mínguez-Vega, Gladys; Gouveia, Amanda Fernandes; Leite, Edson; Andrés, Juan; Longo, Elson
Abstract : In the current communication, the synthesis of metallic Bi nanoparticles with coexisting crystallographic structures (rhombohedral, monoclinic, and cubic) obtained via direct femtosecond laser irradiation of NaBiO3 is demonstrated for the first time. Abstract : In the current communication, the synthesis of metallic Bi nanoparticles with coexisting crystallographic structures (rhombohedral, monoclinic, and cubic) obtained via direct femtosecond laser irradiation of NaBiO3 is demonstrated for the first time. By exploring the use of high laser power values, it is revealed that the promoted laser-mediated reactions lead to the synthesis of coexisting phases in metal nanoparticles, which may be a widely occurring phenomenon in other materials under femtosecond laser irradiation, and a fundamental concern for laser-based nanofabrication.